A field guide to getting lost - Solnit, Rebecca (New York : Viking, 2005)
A series of autobiographical essays draws on key moments and relationships in the author's life to explore such issues as trust, loss, and desire, in a volume that focuses on a central theme of losing oneself in the pleasures of experience.
new book 2023 summer.
Keywords: Solnit, Rebecca -- Travel -- United States; Solnit, Rebecca -- Travel -- West (U S ); Landscapes -- United States; Landscapes -- West (U S ); Travel -- Philosophy; Arts -- Philosophy; United States -- Description and travel; West (U.S.) -- Description and travel